The use of innovative methods in the systemic development of the cognitive competence of future teachers in the system of preschool education (Journal of Pedagogical Inventions and Practices, 2023)
the article reveals the problem of advanced training of a modern teacher of preschool education, on the basis of a structural-functional approach, the main components and conditions for the development of professional competence of teachers of preschool education are revealed. Abstract: the article describes the problem of improvement of professional personal development of the modern teacher of preschool education; on the bases of structural and functional approach it is implemented to obtain the main components and conditionals of improvement of teachers' professional competence of system of preschool education.